Hindu Political Thought and Plato’s View of Democracy in Indonesia - Saputra, I Made Gede Nesa (Jurnal Review Politik, 2025)
Politics is a main pillar in national life, but political practices in Indonesia often deviate from public orientation and favor the interests of the oligarchy. This condition reveals a gap between the political ideal as a means of serving the people and the political reality, which tends to be pragmatic and manipulative. This research fills a gap in the study connecting classical Western political criticism with ethical values in the Hindu tradition. The method used is qualitative with a descriptive-analytical approach through a study of the texts Ramayana, Mahabharata, Arthasastra, Nitisastra, and Negarakertagama, as well as Plato's thoughts on the vulnerability of democracy to oligarchy. The research results show that politics in the Hindu paradigm emphasizes service (sevanam), while Plato's criticism reflects the dangers of oligarchy in democracy. The novelty of this research lies in the integration of these two perspectives to offer a more ethical reflective framework for understanding and correcting the dynamics of contemporary Indonesian politics.